(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
The current research aimed to show the role of kindergarten educators in promoting the concept of the national affiliation of kindergarten children from their Perspectives, The research sample consisted of (104) nanny from private kindergarten teachers in Lattakia for the academic year 2018/2019. The researcher adopted the descriptive approach, And she used as a research tool, which was designed by her and ruled by a group of arbitrators, The results were determined by applying a sample of (34) female kindergarten teachers from outside the research sample by calculating the coefficient of alpha Cronbach (0.886), as well as from the Spearman Brown equation (0.847). The research reached the following: -The role of kindergarten educators in promoting the concept of national belonging to kindergarten children has been high. - There are no differences in the views of kindergarten educators about their role in the development of national belonging to the child according to the variable number of years of experience. - There are differences in the views of kindergarten educators on their role in the development of national belonging to the child according to the variable educational and educational qualification of the educator, for the benefit of both the university leave and diploma of educational rehabilitation. هدف البحث الحالي إلى تعرف دور مربيات رياض الأطفال في تعزيز مفهوم الانتماء الوطني لطفل الروضة من وجهة نظرهن، وقد تكونت عينة البحث من (104) مربية من مربيات رياض الأطفال الخاصة في مدينة اللاذقية للعام الدراسي 2018/2019. اعتمدت الباحثة المنهج الوصفي، واستخدمت الاستبانة كأداة بحث، حيث صممت من قبلها وحكمت من قبل مجموعة من المتخصصين، وتم التأكد من ثباتها بتطبيقها على عينة استطلاعية شملت (34) مربية روضة من خارج عينة البحث، من خلال حساب معامل ألفا كرونباخ، والذي بلغ (0.886)، وكذلك من معادلة سبيرمان براون الذي بلغ (0.847). توصل البحث إلى الآتي: - دور مربيات رياض الأطفال في تعزيز مفهوم الانتماء الوطني لدى طفل الروضة جاء بدرجة مرتفعة. - لا توجد فروق ذات دلالة إحصائية في وجهات نظر مربيات رياض الأطفال حول دورهن في تنمية الانتماء الوطني لدى الطفل وفق لمتغير عدد سنوات الخبرة للمربية. - توجد فروق ذات دلالة إحصائية في وجهات نظر مربيات رياض الأطفال عن بنود الاستبانة حول دورهن في تنمية الانتماء الوطني لدى الطفل وفق متغير المؤهل العلمي والتربوي للمربية لصالح حملة كل من الإجازة الجامعية ودبلوم التأهيل التربوي.